N6-Methyladenosine Modification Patterns and Tumor Microenvironment Immune Characteristics Associated With Clinical Prognosis Analysis in Stomach Adenocarcinoma - Meijing, Zhang; Tianhang, Luo; Biao, Yang (Frontiers in Cell and Developmental Biology, 2022)
N6-methyladenosine (m6A) modification, as part of epigenetic research, has received more and more attention in recent years. The effects of m6A modification on immune cell inﬁltration of the tumor microenvironment (TME) remain largely uncertain in stomach adenocarcinoma (STAD). The Cancer Genome Map (TCGA) database downloaded transcriptome data, clinical-pathological data, and survival data for m6A-regulated genes in 433 STAD tissues that meet the requirements of this study. The Gene Expression Synthesis (GEO) database downloaded GSE84437 data. The correlation between 23 m6A regulated genes was analyzed using R software. Sample clustering analysis was carried out on the genes of the m6A regulatory factor, and survival analysis and differentiation comparison were made for patients in clustering grouping. From the TCGA database, we found that in 94 of the 433 samples (21.71%) there were somatic cell mutations, and ZC3H13 mutations are most common. Based on the consensus matrix k-3 is an optimal choice, we finally identified three different clusterings. Three types of m6A methylation modification patterns were significantly different immune infiltration. A total of 1028 differentially expressed genes (DEGs) were found. The survival analysis of the m6A score found that patients in the high m6A score group had a better prognosis than those in the low m6A score group. Further analysis of the survival curve combining the mutation burden (TMB) and m6A scores found that patients had a significantly lower prognosis in the low tumor mutant group and the low m6A score group (p=0.003). The results showed that PD-L1 was significantly higher in the high m6A score group (p< 2.22e-16). The m6A modification pattern may be an important factor leading to inhibitory changes and heterogeneity in TME. This will facilitate the understanding of TME infiltration characteristics in patients with STAD through the evaluation of the m6A modification pattern.